2013
DOI: 10.1089/jmf.2012.0066
|View full text |Cite
|
Sign up to set email alerts
|

In VitroandIn VivoEffects of Two Coconut Oils in Comparison to Monolaurin onStaphylococcus aureus:Rodent Studies

Abstract: Since monolaurin, a monoglyceride formed in the human body in small quantities, has proven effective both in vitro and in vivo against certain strains of Staphylococcus aureus, an important question arises whether consuming a substance high in lauric acid content, such as coconut oil could increase intrinsic monolaurin production to levels that would be successful in overcoming staphylococcal and other microbial invaders. Both a cup plate method and a microdilution broth culture system were employed to test ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 11 publications
0
17
0
3
Order By: Relevance
“…Staphylococcus aureus, mice treated with GML via oral gavage had alleviated disease burden comparable to mice injected with intraperitoneal vancomycin [139,140]. This suggests that GML may potentially interact with carrier molecules such as serum albumin.…”
Section: Gml As An Antimicrobial Compoundmentioning
confidence: 91%
“…Staphylococcus aureus, mice treated with GML via oral gavage had alleviated disease burden comparable to mice injected with intraperitoneal vancomycin [139,140]. This suggests that GML may potentially interact with carrier molecules such as serum albumin.…”
Section: Gml As An Antimicrobial Compoundmentioning
confidence: 91%
“…; Manohar et al . ). Monolaurin has generally recognised as safe (GRAS) status in the US, is used as an emulsifier in food products and sold as a supplement.…”
Section: Immune‐modulating Effectsmentioning
confidence: 97%
“…Recently, experimental outcomes from many studies discovered that monolaurin had not only antimicrobial activity against various gram-positive and gram-negative bacterial cells [1,3,43] but also antifungal and antiviral properties [44,45,46,47,48]. Manohar et al [49] showed that coconut oils, when used as food flavouring agents, exhibited a wide range of antimicrobial activities. Among MCFAs, LA and its derivatives were found to be the most effective antimicrobial agents for foods and cosmetics [46,50].…”
Section: Antimicrobial Activities Of Virgin Coconut Oilmentioning
confidence: 99%